2012
DOI: 10.1111/j.1748-6653.2012.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of affective prosody in patients at an early stage of relapsing–remitting multiple sclerosis

Abstract: Cognitive dysfunction is well known in patients suffering from multiple sclerosis (MS) and has been described for many years. Cognitive impairment, memory, and attention deficits seem to be features of advanced MS stages, whereas depression and emotional instability already occur in early stages of the disease. However, little is known about processing of affective prosody in patients in early stages of relapsing-remitting MS (RRMS). In this study, tests assessing attention, memory, and processing of affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 92 publications
0
22
1
7
Order By: Relevance
“…Although studies have also investigated vocal 47,48 and bodily affect recognition 38 in this patient group, there were too few to allow inclusion in the current review. In addition, only English-language articles were eligible for inclusion, which led to the exclusion of 2 non-English-language articles found in the electronic search.…”
Section: Resultsmentioning
confidence: 99%
“…Although studies have also investigated vocal 47,48 and bodily affect recognition 38 in this patient group, there were too few to allow inclusion in the current review. In addition, only English-language articles were eligible for inclusion, which led to the exclusion of 2 non-English-language articles found in the electronic search.…”
Section: Resultsmentioning
confidence: 99%
“…Pöttgen established a deficient ability to reason about the mental state of others (ToM) and to have insight into the emotional stages and feelings of others (empathy) in the early stages of RRMS [21,22], even in patients who have no substantial neuropsychological deficits. Emotional prosody comprehension may also be disrupted in the early stages of RRMS [6]. It is argued that this is the earliest social cognitive impairment in patients with MS.…”
Section: Discussionmentioning
confidence: 99%
“…Patients gave less accurate solutions to "discrimination of affective prosody" and more incorrect responses in the subtest "matching of affective prosody to facial expression" for the emotion "anger". Paradoxically, regarding the emotion "fear" they showed better results than controls [6]. Gleichgerrcht et al found that MS subjects (patients n = 38; controls n = 38) had significantly higher self-oriented personal distress (p < 0.01) and higher levels of alexithymia compared to controls [82].…”
Section: Relapsing-remitting Multiple Sclerosis (Rrms)mentioning
confidence: 99%
See 2 more Smart Citations